Forecasting the Trade Flow of Denmark - Lyk-Jensen, Stéphanie Vincent (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
This paper presents the modeling of a dynamic gravity equation in order to forecast the trade flows of goods in and out of Denmark, including transit goods. This analysis is part of a research project where the objective is to establish the future flow of goods for Denmark as well as the node points in order to be able to optimize public investments. The paper only focuses on the construction of the gravity equation that will be used for setting up scenarios for the future flow of goods from and to Denmark. We compare different methods of estimation of the gravity equation used in previous studies and propose a robust estimation of a dynamic gravity equation. Examples of the forecasting method are presented for illustration.